Perlindungan Hukum dan Kepastian Hukum terhadap Perdagangan Data Pribadi dalam UU PDP - Muhammad Rizky; Rini Apriyani; Nur Aripkah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Article 20 of the Personal Data Protection Law (PDP Law) normatively regulates the protection of data subjects and constitutes a pivotal provision that underscores the principle of consent as the legal basis for the processing of personal data for commercial purposes. This normative framework safeguards individuals’ right to privacy, encompassing the validity of explicit consent, the right to withdraw such consent, and the accountability of data controllers. In parallel, Articles 65 to 70 of the PDP Law substantively establish various categories of criminal offenses within the context of personal data protection. These include the unlawful acquisition, disclosure, processing, falsification, and utilization of personal data. Collectively, these provisions reflect the State’s commitment to ensuring criminal legal protection against violations of personal data.This research adopts a doctrinal legal methodology with a descriptive-normative approach to address two primary issues: First, to examine and identify the scope of legal protection concerning the trade of personal data under the PDP Law; and Second, to assess and determine the degree of legal certainty afforded to the trade of personal data within the framework of the PDP Law.Notwithstanding the protective intent embodied in Article 20—particularly concerning the commercial use of personal data—this provision gives rise to legal uncertainty due to the absence of comprehensive regulatory clarity on several critical aspects. Similarly, Articles 65 to 70 continue to exhibit significant legal ambiguities, particularly with respect to the constituent elements of offenses, the definition of harm, corporate liability, regulatory overlap with other legislative instruments, and the lack of clear enforcement mechanisms and implementing institutions.